2018
DOI: 10.3390/molecules23040906
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of CO2 with the Azoles: Tetrel Bonds, Hydrogen Bonds and Other Secondary Interactions

Abstract: Ab initio MP2/aug’-cc-pVTZ calculations have been performed to investigate the complexes of CO2 with the azoles pyrrole, pyrazole, imidazole, 1,2,3- and 1,2,4-triazole, tetrazole and pentazole. Three types of complexes have been found on the CO2:azole potential surfaces. These include ten complexes stabilized by tetrel bonds that have the azole molecule in the symmetry plane of the complex; seven tetrel-bonded complexes in which the CO2 molecule is perpendicular to the symmetry plane; and four hydrogen-bonded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Nor is there a limitation to planar geometries, as π-holes are also common in linear molecules, such as the area above the C atom of CO 2 [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ], OCS [ 49 , 50 , 51 ], N 2 O, and CS 2 [ 52 , 53 , 54 ]. Just as their σ-hole analogs facilitate attractions toward a nucleophile, the same is true of these π-holes.…”
Section: Introductionmentioning
confidence: 99%
“…Nor is there a limitation to planar geometries, as π-holes are also common in linear molecules, such as the area above the C atom of CO 2 [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ], OCS [ 49 , 50 , 51 ], N 2 O, and CS 2 [ 52 , 53 , 54 ]. Just as their σ-hole analogs facilitate attractions toward a nucleophile, the same is true of these π-holes.…”
Section: Introductionmentioning
confidence: 99%
“…A few isolated systems (carbenes, guanidines and more recently phosphines) or combined in the form of frustrated Lewis pairs have been described to be able to react with CO 2 and form covalent aggregates . The mechanism and environment effect of the sequestration and activation of CO 2 has been studied theoretically by different groups …”
Section: Introductionmentioning
confidence: 99%
“…[11,12] The mechanism and environment effect of the sequestration and activation of CO 2 has been studied theoretically by different groups. [13][14][15][16][17][18][19][20] Phosphatrane molecules are a tricyclic cage-like heterocycles which present the possibility to have a transannular dative bond with a nitrogen or another heteroatom. The pioneer synthetic work in the groups of Alder and Verkade [21][22][23][24][25][26][27][28][29] showed that depending of the size, substituents and environment they can adopt out:out and/or in:out conformations.…”
Section: Introductionmentioning
confidence: 99%
“…The binding distances and interaction energies of these complexes are listed in Table 1 . According to the previous studies [ 37 , 62 , 65 , 67 , 84 , 85 ], the formation of such anionic tetrel-bonding interactions can be largely attributed to the localization of a positive electrostatic potential over the M atom, in the extension of the M-X bond. Indeed, the MEP analysis of XF 3 M monomers in Figure 1 reveals that the maximum positive electrostatic (V S,max ) of the Sn atom (96.5 kcal/mol) in SnF 4 is greater than that of Ge (70.2 kcal/mol) and Si (57.3 kcal/mol) in GeF 4 and SiF 4 , respectively.…”
Section: Resultsmentioning
confidence: 99%